1995
DOI: 10.1016/s0006-3495(95)80212-2
|View full text |Cite
|
Sign up to set email alerts
|

Luminal calcium regulates calcium release in triads isolated from frog and rabbit skeletal muscle

Abstract: Triads isolated from frog and rabbit skeletal muscle were equilibrated with different external [Ca2+], ranging from 0.025 to 10 mM. Vesicular calcium increased with external [Ca2+] as the sum of a linear plus a saturable component; the latter, which vanished after calsequestrin removal, displayed Bmax values of 182 and 132 nmol of calcium/mg of protein, with Kd values of 1.21 and 1.14 mM in frog and rabbit vesicles, respectively. The effect of luminal [Ca2+] on release kinetics in triads from frog and rabbit s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 38 publications
(35 reference statements)
5
63
1
Order By: Relevance
“…Fig. 1), and such responses can be elicited many times provided that the fibre is repolarized in the high [K+] (Lamb & Stephenson, 1990a (Donoso, Prieto & Hidalgo, 1995;Sitsapesan & Williams, 1995). Measurement of total Ca2+ content of a muscle fibre After determining the response of a skinned muscle fibre to depolarization, the total amount of Ca2+ contained in the fibre could be quantified by pre-equilibrating the fibre in a solution with a particular [BAPTA] for 30 s and then transferring the fibre to a TX-oil emulsion in order to lyse all membranous compartments and release any Ca2+ within, as described by Fryer & Stephenson (1996).…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 1), and such responses can be elicited many times provided that the fibre is repolarized in the high [K+] (Lamb & Stephenson, 1990a (Donoso, Prieto & Hidalgo, 1995;Sitsapesan & Williams, 1995). Measurement of total Ca2+ content of a muscle fibre After determining the response of a skinned muscle fibre to depolarization, the total amount of Ca2+ contained in the fibre could be quantified by pre-equilibrating the fibre in a solution with a particular [BAPTA] for 30 s and then transferring the fibre to a TX-oil emulsion in order to lyse all membranous compartments and release any Ca2+ within, as described by Fryer & Stephenson (1996).…”
Section: Resultsmentioning
confidence: 99%
“…Early studies in permeabilized hepatocytes provided evidence that an increase of intraluminal Ca 2ϩ levels increased the sensitivity of IP 3 receptors to IP 3 (Nunn and Taylor, 1992). Although subsequent studies confirmed a positive effect of intraluminal Ca 2ϩ on IP 3 receptors (Parys et al, 1993) (Donoso et al, 1995). Recordings of single RyR channels of native RyRs in SR vesicles in the presence of Mg-ATP using Cs ϩ as the charge carrier showed that raising luminal Ca 2ϩ concentration from 20 M to 5 mM increased the open channel probability .…”
Section: Regulation Of Ca 2ϩ Within the Endoplasmic Reticulummentioning
confidence: 94%
“…1 C) (Lee, 1993). In addition to these cytosolic regulators of release, there are indications that the level of calcium within the lumen of the ER/SR might be capable of adjusting the sensitivity of both the InsP3Rs (Missiaen, Taylor & Berridge, 1992;Parys, Missiaen, De Smedt & Casteels, 1993;Horne & Meyer, 1995;Tanimura & Turner, 1996) and the RyRs (Donoso, Prieto & Hidalgo, 1995;Lukyanenko, Gyorke & Gyorke, 1996). Overloading cardiac myocytes results in a marked increase in the excitability of the RyRs, which is manifested by the appearance of regenerative calcium waves (Cheng, Lederer & Cannell, 1993;Cheng, Lederer, Lederer & Cannell, 1996a).…”
Section: Basic Aspects Of Calcium Signallingmentioning
confidence: 99%